Peningkatan Keterampilan Dan Pengetahuan Make Up Natural Flawless Bagi Remaja Puteri Di Kelurahan Karuwisi Utara Kota Makassar: Id - Izmi Burhanuddin; Andi Nur Maida (V-MACHINE: Vocational and Mechanical Community Service Journal, 2024)
Enhancement of makeup skills with a natural flawless look is becoming increasingly popular among teenage girls in Makassar City. This look emphasizes natural beauty, with a fresh and understated finish. This research aims to explore effective methods and techniques to improve natural flawless makeup skills among teenage girls. The methods used include training sessions, workshops, lectures, and practical tutorial demonstrations focusing on the preparation of tools, materials, and cosmetics, the correct use of products, and appropriate application techniques. The research results show that the teenage girls who participated in this program experienced a significant improvement in their understanding and skills in applying natural flawless makeup. They also reported an increase in confidence in expressing themselves through makeup. This study suggests the need for further education and access to supportive resources for teenage girls to develop their makeup skills responsibly and creatively, potentially leading to new business opportunities Keywords: Enhancement, Skill, Makeup, Natural,Flawless